2015
DOI: 10.1021/la5046767
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Thiolate Readsorption on the Quality of Mixed Monolayers Formed through an Electrochemcial Method

Abstract: Lateral Force Microscopy (LFM) was used to probe the quality of binary mixed monolayers formed on planar polycrystalline gold through an electrochemical method. In the approach, portions of a self-assembled monolayer (SAM) composed of 2-aminoethanethiol (AET) were removed from the Au(111) surface facets by selective reductive desorption which maintained undisrupted regions of AET elsewhere on the polycrystalline surface. Monolayer voids created by this method were backfilled with 11-mercaptoundecanoic acid (MU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
(104 reference statements)
0
4
0
Order By: Relevance
“…Control over the preparation of mixed component alkylthiolate self-assembled monolayers (SAMs) via electrochemical treatment has been demonstrated by manipulating the substrate potential during SAM deposition and via the reductive desorption of a portion of the monolayer. This is possible since the potential of SAM reductive desorption is sensitive to the substrate surface crystallography. Removal from Au(111) occurs at the least negative reduction potential while a more negative potential is required for more open surfaces (e.g., 210).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Control over the preparation of mixed component alkylthiolate self-assembled monolayers (SAMs) via electrochemical treatment has been demonstrated by manipulating the substrate potential during SAM deposition and via the reductive desorption of a portion of the monolayer. This is possible since the potential of SAM reductive desorption is sensitive to the substrate surface crystallography. Removal from Au(111) occurs at the least negative reduction potential while a more negative potential is required for more open surfaces (e.g., 210).…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical potential has also been used to remove the SAM from specific surface regions which were then backfilled with a different thiol. The resulting surface was analyzed using lateral force AFM which distinguished the short- and long-chained alkylthiolates. , In addition to reductive desorption of alkanethiolate SAMs, oxidative desorption has been demonstrated, however, with less control over the specificity of the surface feature removed . Control over the surface coverage of thiolated DNA on gold was also demonstrated by reductive desorption in the presence of a short chain alkylthiol. , …”
Section: Introductionmentioning
confidence: 99%
“…In situ ellipsometry study of mixed monolayers showed evidence for the formation of a low refractive index region aer desorption of the monolayer component. 14 In a lateral force microscopy study of some binary monolayers formed on planar polycrystalline gold, 15 portions of 2-aminoethanethiol were removed by selective reductive desorption and backlled with 11-mercaptoundecanoic acid. Phase formation in mixed alkanethiol monolayers 16 was also revealed by electrochemical quartz crystal nanobalance.…”
Section: Introductionmentioning
confidence: 99%
“…These devices should also possess surface functionalities that can effectively interact with gaseous or solution species of interest, leading to the generation of characteristic electronic and/ or optical signals [10][11][12][13]. In particular, there is a growing demand for the preparation of a multifunctional surface with a well-defined topographical structure, which would expedite the collection and analyses of complexed signals from various analytes [14][15][16] Various fabrication strategies, such as lithography [17][18][19], self-assembled monolayers (SAMs) [20][21][22][23][24], electrochemical treatment [25], and electro-polymerization [26] are available for the functionalization of an inorganic surface. Of these methods, the SAMs technique, in which organic molecules are spontaneously bound to an inorganic surface, has been the most widely used and investigated.…”
Section: Introductionmentioning
confidence: 99%